Analysis And Management Of Polychlorinated Biphenyls (Pcbs) At Temporary Storage Of Hazardous And Toxic Waste Of Pln Up3 Tanjung Karang - Romi Sepsriza; Dikpride Despa; FX. Arinto Setyawan; Rinawati Rinawati (Jurnal Health Sains, 2022)
Polychlorinated Biphenyls (PCBs) are persistent organic pollutants that harm the environment and human health. One of its uses is in the transformer at the electricity company. Efforts to prevent PCB contamination are carried out through identification and inventory, management of PCBs, and monitoring of PCBs. The methods used in this study were direct observation, questionnaires, and PCB testing using the Dexsil L2000DX/Chloride Analyzer as early detection of the presence of PCBs in offline transformer oil and sorting out samples with chloride concentrations > 50 ppm. The data collected is in the form of primary data and secondary data. The purpose of this research is to implement an Environmental Safeguard, especially PCBs at PLN UP3 TPS Tanjung Karang Hazardous and Toxic Material Waste, so there will be no pollution to the surrounding environment